Association of methanogenic bacteria with rumen ciliates. - Vogels, G D (1980)
In 11 species of rumen ciliates belonging to nine genera of the family Ophryoscolecidae (order Entodiniomorphida) an ectosymbiosis with methanogenic bacteria was found. The bacteria could be identified as methanogens on the basis of the presence of specific fluorescent coenzymes (F350 and F420). This somatic interaction may reflect a metabolic interaction in which efficient interspecies hydrogen transfer benefits both partners.